2017
DOI: 10.1002/chem.201604886
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Binding Properties, and Differences in Cell Uptake of G‐Quadruplex Ligands Based on Carbohydrate Naphthalene Diimide Conjugates

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…In the search for G4-selective ligands as novel anticancer drugs, naphthalene diimides (NDIs) emerged as promising compounds for their ability to interact with G-tetrads. Among the many advantages of NDIs, the most noteworthy are their chemical accessibility and possibility to easily functionalize their aromatic cores with multiple diverse pendant groups, thus allowing a fine modulation of their properties, and particularly of their affinity toward different secondary structure-forming oligonucleotides [7][8][9][10]. For these peculiar features, NDIs have been extensively studied both as fluorescent probes and oligonucleotide-targeting ligands [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for G4-selective ligands as novel anticancer drugs, naphthalene diimides (NDIs) emerged as promising compounds for their ability to interact with G-tetrads. Among the many advantages of NDIs, the most noteworthy are their chemical accessibility and possibility to easily functionalize their aromatic cores with multiple diverse pendant groups, thus allowing a fine modulation of their properties, and particularly of their affinity toward different secondary structure-forming oligonucleotides [7][8][9][10]. For these peculiar features, NDIs have been extensively studied both as fluorescent probes and oligonucleotide-targeting ligands [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the substitution pattern of their core, as well as the chemical nature of their substituents, plays a crucial role in NDI G4 binding, as well as in G4 vs. duplex DNA selective recognition [8,13]. In this context, some of us recently synthesized a set of NDIs derivatized with alkylamine substituents on the naphthalene core [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This provides many potential opportunities to exploit G4 for the development of new therapeutic strategies. Indeed, our own research groups and many others have reported work driven towards the identification of new G4 ligands as the basis of anticancer, and antiparasitic, therapies. The vast majority of G4 ligands employ rigid aromatic heterocyclic frameworks that are designed to π‐stack onto the large surface of the G‐tetrads .…”
Section: Introductionmentioning
confidence: 99%
“…[10] It also has been proved that G-quadruplex structures formed in G-rich telomeric DNA can inhibitt elomerase activity. [27,28] Our group has been workingo nd esigning novel G4 ligands with improveds pecificity for recognizingG -quadruplex, [29][30][31] and previously we reported cyclic naphthalene diimidec oupling with cyclohexane( cNDI-ch),w hich exhibited as ignificantly highera ffinity( 260-fold) towards binding with G-quadruplex than double-stranded DNA. [14] In addition, some reports already suggested that the G-quadruplex structure in the telomeric sequence assembled like beads on as tring, [15,16] G4 ligands which can selectively target multiple G4 repeats might be promisingf or furthere nhanced specificity on inhibiting telomerase function, and are attractingmore attentionf rom Gquadruplex researchers.…”
mentioning
confidence: 99%
“…Over the past several years, some ligandd imers [17][18][19][20][21][22][23][24] and tetramers [25] have been reported with a stronga bility to recognize dimerico rm ultiple G-quadruplex structures,w hich is supportedb yt he fact that the G4 ligand multimer might be ag ood model for stabilizing G-quadruplex repeats.As one important G4 ligand, naphthalene diimide can recognize the G-quadruplex structure through p-p stacking, [26] and its binding affinity to G-quadruplexw as rarely affected even underi nv ivo mimic molecular crowding conditionsa nd may represent superior telomerasei nhibitors in cell nuclei. [27,28] Our group has been workingo nd esigning novel G4 ligands with improveds pecificity for recognizingG -quadruplex, [29][30][31] and previously we reported cyclic naphthalene diimidec oupling with cyclohexane( cNDI-ch),w hich exhibited as ignificantly highera ffinity( 260-fold) towards binding with G-quadruplex than double-stranded DNA. [29] In addition, Chiara Marchetti et al also reported similar macrocyclic naphthalened iimides coupling with the phenylring, which exhibited ah igh selectivity for the G-quadruplex structure and showeda ntiproliferative effectso nc ancerl ines with al ow range of concentrations.…”
mentioning
confidence: 99%